Cardiovascular safety of the dipetidyl peptidase‐4 inhibitor alogliptin in type 2 diabetes mellitus1. Issue 7 (4th April 2013) - White, W. B.; Pratley, R.; Fleck, P.; Munsaka, M.; Hisada, M.; Wilson, C.; Menon, V.
<x xml:space="preserve">Abstract</x> Aim As there have been concerns that some classes or agents for the treatment of type 2 diabetes may increase CV risk, we evaluated the cardiovascular profile of the dipeptidyl peptidase‐4 inhibitor alogliptin. Methods We evaluated the incidence of CV events in patients treated with alogliptin, placebo or comparator antihyperglycaemic drugs in the clinical trial database for alogliptin using the composite major adverse cardiovascular event (MACE) endpoints of CV death, non‐fatal myocardial infarction and non‐fatal stroke. Results The pooled analysis included 4168 patients exposed to alogliptin 12.5 and 25 mg daily for 2023 patient‐years compared to 691 patients treated with placebo for 263 patient‐years and 1169 patients treated with other antidiabetic agents (metformin, sulfonylureas and thiazolidinediones) for 703 patient‐years. CV events were adjudicated by an expert endpoint committee blinded to treatment allocation. The incidence rates of the combined MACE were not significantly different between patients treated with alogliptin and comparator therapies (hazard ratio=0.635, 95% confidence interval, 0.0, 1.41). Additionally, other types of serious CV events were not significantly different between patients treated with alogliptin and comparator therapies. Conclusion These analyses have not shown a signal of increased CV risk with alogliptin in patients with type 2 diabetes. Future results from the adequately powered EXAMINE trial will definitively assess the CV safety profile of aloglipin in patients with type 2 diabetes mellitus.